Speech by the Hon’ble Chief Minister Penang at the Regional Official Launching of the Masmara One Way Package Tour at the E&O Hotel Penang on Saturday 17th July 1976. - Lim, Chong Eu (1976)
The Hon’ble Chief Minister Penang, Dr. Lim Chong Eu, has asked me to convey his sincere apologies for not being able to be present today at the Official Launching of Masmara One Way Package Tour and he asked to represent him and read out his speech.